Driving the fake out of public administration : detoxing HR in the Canadian federal public sector - Hubbard, Ruth, 1942-; Paquet, Gilles, 1936- (Invenire, 2016)
"This book deals with the fake at the origin of much unwarranted waste and inefficiency in the Canadian federal public administration. The authors propose that it has its sources in the progressivist cosmology that has displaced the primary concern of government from coordination to distribution. They probe the world of human resources (HR) as an illustration of the malefits entailed by this displacement of focus which occurred dramatically in 1967 when the Government of Canada decided to care less about performance and more about being a 'model employer.' An MRI of the HR systems helps to guide a process of modernisation of the HR regimes. But the reader is sharply reminded in the conclusion that one cannot detox the HR regimes without tackling the progressivist cosmology."--